Pengaruh Financial Literacy, Self-Control, dan Sikap Keuangan terhadap Perilaku Pengelolaan Keuangan Pribadi pada Penggemar Musik Hindia Kota Semarang - Nabilla Oktafiana Putri; Linda Ayu Oktoriza; Suhita Whini Setyahuni; Rudi Kurniawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The purpose of this study is to determine how Indian music fans in Semarang manage their personal finances, taking into account their knowledge, self-control, and perspectives on finance.. This research was conducted using a quantitative method through an online survey of 160 respondents who met the criteria. Measurement models and structural models were tested to analyze the data using SmartPLS. The results of the study indicate that the three independent variables have a positive and significant influence on how individuals manage their finances. The highest f2 value (0.241) and the highest T-statistic value (5.862) indicate that financial attitude is the dominant factor among the three variables. Approximately 56.6% of the differences in financial management behavior can be attributed to the research model, while the remaining variables outside the model influence it. The results show that young people who frequently attend concerts and entertainment activities have more conscious financial behavior, especially those with good financial knowledge, self-control, and a positive attitude toward finance. This study recommends community-based financial education to help music fans manage their expenses better.